Word Weapons? Letters to Editors - Stewart, Georgina Tuari (Philosophy of Education Society of Australasia, 2021)
This short commentary argues that academic letters to editors on politically-contested topics must be treated with particular ethical care. The interface between science and Māori/Indigenous knowledge is one such topic, vulnerable to inadequate but commonly-held ideas about both science and Māori/Indigenous knowledge. Letters to editors by scientists are personal opinion but carry the imprimatur of science expertise. When such letters contain lay views masquerading as expert opinion, they have negative effects on both science and Māori knowledge, hence qualifying to be described as ‘word weapons’.
Keywords: Academic freedom; Editorial practice; Letters to editors; Mātauranga Māori/Māori knowledge; Publishing ethics